Creativity Development of Children 5-6 years old Through Loose Parts Media - Susanti, Fitri Maulida; Hidayati, Sri; Aghnaita, Aghnaita; Muzakki, Muzakki (PIAUD Universitas Islam Negeri Sunan Kudus, 2023)
Loose parts media is media that can be moved, combined, redesigned, aligned, separated, and put together in various ways that can develop children’s creativity. The purpose of this study is to describe the creativity of children aged 5-6 years through loose parts media. The research subjects were 1 class teacher and 14 class B2 students. The research methodology used is descriptive qualitative. The data collection techniques are through observation, interviews, and documentation. Based on the results of the study, the available loose parts media components were natural materials, plastics, used packaging, glass and ceramics, threads and fabrics, and metals. The development of creativity in class B2 children through loose parts media has been good, covering several indicators. Namely: likes to explore the environment, likes to observe, and hold everything, has great curiosity, spontaneously expresses thoughts and feelings, likes to experiment and try new things, rarely feels bored, and has high imagination power.